The Moderating Role of Wedge-Control Ownership on the Relationship between Board Structure and Dividend Policy - Mustafa, Adil Abdulqader; Yusoff, Wan Sallha; Mustafa, Aree Saeed (The journal of contemporary issues in business and government, 2023)
Purpose: This study explores the impact of board structure on dividend payment policy. Method: The study examined a sample of non-financial firms listed on the Borsa Istanbul (BIST) from 2016 to 2020. The board structure was represented by the size of the board, board independence, female board membership, and board knowledge/skills in the research. Meanwhile, control wedge ownership was used as a moderating variable. In addition, two control factors were added, including return on equity and firm age. The study's dependent variable was the dividend per share, which represented the company's dividend payout policy. Findings: The regression analysis showed that the dividend policy was strongly linked with board size, female board membership, and knowledge/skill. On the other hand, the board independence variable exhibited a non-significant positive outcome, contrary to expectations. However, according to the findings, three of the four interaction associations examined are significant at the one and five-percent levels. The significance of the other interaction was determined to be negligible. Novelty: This study is different from previous research because this study is the first to examine The Moderating Role of Wedge-Control Ownership on the Relationship between Board Structure and Dividend Policy.